2008
DOI: 10.1080/14616710802037466
|View full text |Cite
|
Sign up to set email alerts
|

Rent Regulation: The Balance between Private Landlords and Tenants in Six European Countries

Abstract: The private rental sector has been declining in many European countries. In describing the decline of the private rental sector, it is often suggested that a causal relationship exists between the decrease in private renting and rent control. The assumption is that the stricter the form of rent control, the greater the decrease in private renting levels. Or, conversely, that with fewer rent controls there are more opportunities for the private rental sector. At the same time, however, an unregulated rental mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 10 publications
2
40
0
2
Order By: Relevance
“…Whilst there has been comparative research into rent setting and regulation (e.g. Haffner et al, 2008), there appears to have been no systematic operationalisation and testing of the assumptions about security of tenure or housing quality. It has also been suggested that privatization processes from early 1990s (i.e.…”
Section: De Jure De Facto and Perceptual Security Of Tenurementioning
confidence: 98%
“…Whilst there has been comparative research into rent setting and regulation (e.g. Haffner et al, 2008), there appears to have been no systematic operationalisation and testing of the assumptions about security of tenure or housing quality. It has also been suggested that privatization processes from early 1990s (i.e.…”
Section: De Jure De Facto and Perceptual Security Of Tenurementioning
confidence: 98%
“…Though rent control is primarily related to government policy to secure affordability on the private rented sector (e.g., Haffner et al 2008), rent control is applied to both private and social housing sectors. Most studies on the effects of rent control have, however, focused on the impact of rent controls on the earning potential of private landlords and on their decisions on maintenance (Arnott and Shevyakhova 2014; Lind 2015), investments and the sale of rental housing (e.g., Andrews et al 2011; Autor et al 2012; Block and Olsen 1981).…”
Section: Rent Control and Price Settingmentioning
confidence: 99%
“…This is despite quantitative analysis which argues that the introduction of various types of rent control in England would have very little effect on landlords' incomes and profit margins (Clarke, Hamilton, Heywood, & Udagawa, 2015). The political reluctance to consider methods of rent control differs from other European contexts, which use different forms of control that may restrict the rate and frequency of rent rises within tenancies (Haffner, Elsinga, & Hoekstra, 2008).…”
Section: Affordabilitymentioning
confidence: 99%